2021
DOI: 10.3390/agronomy11071430
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Seed Production Environment on Seed Development and Quality of Soybean (Glycine max (L.) Merrill)

Abstract: The aim of the study was to determine the effect of seed production environment in Sri Lanka on seed development, maturation, and subsequent seed quality. The experiment was conducted at six production environments, three locations (Mahailluppalama (M1), Polonnaruwa (POL), and Aluttarama (ALU), over two planting cycles (P1, P2). Seed development and maturation, seed and seedling quality characteristics were evaluated at five reproductive (R6, R7, R8, R8 + 5 and R8 + 10) maturity stages. The study infers that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…CCI Showed a positive correlation with yield per plant and negative with oil% and protein%, oil% and protein% showed a negative correlation with LAI, LAD, CCI, and seed yield per plant. Similar results were obtained by Adetokunbo et al [4], Upadhyay et al [5], Mehra et al [6], Weerasekara et al [7], Ogunkanmi et al [8], Soni et al [9], showed similar results .…”
Section: Resultssupporting
confidence: 85%
“…CCI Showed a positive correlation with yield per plant and negative with oil% and protein%, oil% and protein% showed a negative correlation with LAI, LAD, CCI, and seed yield per plant. Similar results were obtained by Adetokunbo et al [4], Upadhyay et al [5], Mehra et al [6], Weerasekara et al [7], Ogunkanmi et al [8], Soni et al [9], showed similar results .…”
Section: Resultssupporting
confidence: 85%
“…The soybean varieties reached maturity in 85 days in a dry environment while in wet conditions the DM extended to 97 days (Weerasekara et al, 2021). The Leaf area (LA) among the varietal lines of soybean varied between 6.7 ± 0.31 cm2 (NIBGE 41) and 37.2 ± 0.31 cm2 (NIBGE 1).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of CAT and POD activities was highest (21.4 mmol/min/mg FW and 83.7 nmol/min/mg FW, respectively) at the time of harvest, which gradually declined with the increase in storage period, amounting to only 6.2 µmol/min/mg FW and 24.6 nmol/min/mg FW, respectively, for CAT and POD activities by the end of the 12 months storage. The weakening of antioxidant defense mechanism resulted in low seed and seedling quality performance [2,39]. Several studies suggested that priming triggers the ROS scavenging process by increasing antioxidant (SOD, CAT, POD and APX) activities and enhanced stress bearing ability of the seedling [11], [38,40].…”
Section: Discussionmentioning
confidence: 99%
“…De Vitis et al [1] reported that seed deterioration is an inevitable process, even under proper storage conditions. Thus, all seeds undergo deterioration during storage, differing in rate depending on initial seed quality [2] and storage environment [3,4]. In third world countries, tropical in nature, the deterioration is enhanced when seeds are stored under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%